Pengaruh Kecerdasan Adversitas dan Minat Menjadi Guru Terhadap Kesiapan Menjadi Guru Mahasiswa Prodi Pendidikan Ekonomi Universitas Pendidikan Ganesha - Suryaningsih; Kadek Rai Suwena (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to examine: (1) the effect of adversity intelligence on the readiness to become a student teacher of the Economics Education Study Program class of 2019, (2) the effect of interest in becoming a teacher on the readiness to become a teacher of students of the Economics Education Study Program class of 2019, and (3) the effect of adversity intelligence and interest becoming a teacher on the readiness to become a teacher for students of the Economics Education Study Program class of 2019. This research uses a descriptive approach and the type of data is quantitative. The total sample is 76 students from class 2019. Sampling uses saturated sampling. Methods of data collection using a questionnaire with the method of data analysis, namely multiple linear regression analysis. The hypothesis test uses the t test and F test which are processed with the help of SPSS 16 for windows. The results of this study indicate that: (1) adversity intelligence has a positive and significant impact on readiness to become a teacher with a value of tcount> ttable, namely 3.078> 1.665, (2) interest in becoming a teacher has a positive and significant effect on readiness to become a teacher with a value of tcount> ttable which is equal to 5.699> 1.665, and (3) adversity intelligence and interest in becoming a teacher have a positive and significant effect on readiness to become a teacher with a value of fcount>ftable which is equal to 63.344> 3.12.